Structural Variation of the X Chromosome Heterochromatin in the Anopheles gambiae Complex - Sharma, Atashi (Genes (Basel), 2020)
Heterochromatin is identified as a potential factor driving diversification of species. To understand the magnitude of heterochromatin variation within the Anopheles gambiae complex of malaria mosquitoes, we analyzed metaphase chromosomes in An. arabiensis, An. coluzzii, An. gambiae, An. merus, and An. quadriannulatus. Using fluorescence in situ hybridization (FISH) with ribosomal DNA (rDNA), a highly repetitive fraction of DNA, and heterochromatic Bacterial Artificial Chromosome (BAC) clones, we established the correspondence of pericentric heterochromatin between the metaphase and polytene X chromosomes of An. gambiae. We then developed chromosome idiograms and demonstrated that the X chromosomes exhibit qualitative differences in their pattern of heterochromatic bands and position of satellite DNA (satDNA) repeats among the sibling species with postzygotic isolation, An. arabiensis, An. merus, An. quadriannulatus, and An. coluzzii or An. gambiae. The identified differences in the size and structure of the X chromosome heterochromatin point to a possible role of repetitive DNA in speciation of mosquitoes. We found that An. coluzzii and An. gambiae, incipient species with prezygotic isolation, share variations in the relative positions of the satDNA repeats and the proximal heterochromatin band on the X chromosomes. This previously unknown genetic polymorphism in malaria mosquitoes may be caused by a differential amplification of DNA repeats or an inversion in the sex chromosome heterochromatin.